Microbial inactivation using pulsed light - a review - Kundwal, Moses Elisha (Penerbit UTM Press, 2015)
The use of pulse light to inactivate microbes has recently attracted interest of many researchers. Consequently, there are various reports on the efficacy and advantages of pulsed light in microbial inactivation; and also the potentiality of pulsed light systems being adopted for industrial use in this regards. Here, we review some of the works done in relation to microbial inactivation with pulse light, with emphasis on the role played by pulse light parameters such as fluence, spectral range, pulse power, pulse width, pulse frequency, etc. We focussed in particular on factors that make pulsed light systems more effective than their continuous wave counterpart and also proffer suggestions on possible areas for improvement in future study. The use of pulsed lasers in inactivating microbes was briefly appraised. Also, prospects and challenges in the use of pulsed light for inactivation were highlighted.